2006
DOI: 10.1111/j.1365-2958.2006.04986.x
|View full text |Cite
|
Sign up to set email alerts
|

A slipped‐mispairing mutation in AgrA of laboratory strains and clinical isolates results in delayed activation of agr and failure to translate δ‐ and α‐haemolysins

Abstract: Summaryagr is a global regulator of staphylococcal virulence and other accessory gene functions, especially including the haemolysins. Lack of haemolysin production therefore generally represents a defect in agr function. An example of this is Staphylococcus aureus strain RN4220, a widely used laboratory strain that carries a nitrosoguanidine (MNNG)-induced mutation enabling it to accept DNA from Escherichia coli and other bacteria. We show here that the nonhaemolytic phenotype of RN4220 is caused by an extra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
148
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(159 citation statements)
references
References 35 publications
10
148
1
Order By: Relevance
“…The same experiment was performed on RN4220 (strain EL101), which is capable of accepting foreign DNA, 39,40 and which produces low levels of RNAIII. 41 First, we have verified by Northern blot analysis the levels of lytM mRNA in backgrounds HG001 and RN4220 ( Fig. 2A).…”
mentioning
confidence: 99%
“…The same experiment was performed on RN4220 (strain EL101), which is capable of accepting foreign DNA, 39,40 and which produces low levels of RNAIII. 41 First, we have verified by Northern blot analysis the levels of lytM mRNA in backgrounds HG001 and RN4220 ( Fig. 2A).…”
mentioning
confidence: 99%
“…Most RRs interact with DNA through a recognition alpha helix located within a DNA binding domain. Studies of the S. aureus AgrA (accessory gene regulator A), a LytTR RR, have provided insight into the LytTR-DNA interaction (Koenig et al 2004;Nicod et al 2014;Rode et al 2007;Sidote et al 2008;Traber and Novick 2006). AgrA is a cytoplasmic protein that possesses an N-terminal REC domain of 124 amino acids and a C-terminal LytTR domain of 98 residues.…”
Section: The Atcsr Two Component Regulatory System and The Lyttr Domainmentioning
confidence: 99%
“…However, S. aureus agr dysfunction has also been associated with longer duration of bacteremia and attenuated vancomycin bactericidal activity, as well as increased mortality among bacteremic patients (4,13). A number of reports have indicated that the emergence of vancomycin-intermediate S. aureus (VISA) was accompanied by agr dysfunction, mainly due to loss-offunction mutations within the agr operon (11,12,18).…”
mentioning
confidence: 99%
“…AgrA also activates the agr P3 promoter, which drives the synthesis of RNAIII, the effector of target gene regulation. RNAIII also encodes ␦-hemolysin, the expression of which serves as a surrogate for agr functionality (5,18,19).…”
mentioning
confidence: 99%